The Role of 18F-FDG-PET/CT in Infectious Endocarditis and Cardiac Device Infection - Isabella Rewers, Kate; Mathias Scholtens, Asbjorn; Thomassen, Anders; Hess, Soren (Current Molecular Imaging (Discontinued), 2014)
As in many other infectious diseases 2-deoxy-2-[18F] fluoro-D-glucose (18F-FDG) positron emission tomography (PET) combined with computed tomography (CT) (18F-FDG-PET/CT) has shown obvious potential in cardiovascular infections, although several issues remain unclarified with regard to acquisition and patient preparation protocols. Overall, 18F-FDG-PET/CT should be considered an important complementary diagnostic technique in infectious endocarditis, and cardiac device related infections, especially for extracardiac disease state. Also, monitoring of the metabolic response to antibiotics should be considered a promising indication, and the high negative predictive value of 18F-FDG-PET/CT is also of great clinical relevance. The purpose of this work was to present the current evidence regarding the role of 18F-FDGPET/ CT in infectious endocarditis, extracardiac complications, and cardiac implantable electronic devices.
Keywords: 18F-FDG-PET/CT